Generations & geographies in the visual arts: feminist readings - Pollock, Griselda.. (Routledge, 1996)
In Generations and Geographies, the challenge of contemporary feminist theory encounters the provocation of the visual arts made by women in the twentieth century. The major issue is difference: sexual, cultural and social. Generations points to the singularity of each artist's creative negotiation of time and historical and political circumstance; Geographies calls attention to the significance of place, location and cultural diversity, connecting issues of sexuality to those of nationality, imperialism, migration, diaspora and genocide.Generations and Geographies is framed by theoretical debates in cultural analysis by Griselda Pollock, Mieke Bal, Elisabeth Bronfen and Irit Rogoff, and two historical analyses of representations of the female nude by Rosemary Betterton and Nanette Salomon. Essays on international contemporary art discuss artistic practice by women working in both western and non-western contexts, focusing on themes of the mother, the body, the land and history/memory. The artists discussed include the French performance artist Orlan, the Cuban American artist Ana Mendieta and Jenny Saville from Britain, the Chilean artist Cecilia Vicuna, Shimada Yoshiko from Japan, the Korean artist Re-Hyun Park and the Korean/Canadian artist Jin-me Yoon, Bracha Lichtenberg Ettinger from Israel and the American artist Cindy Sherman. British/Zanzibari artist Lubaina Himid provides specially commissioned artists' pages on the theme of history, location and displacement.
Keywords: 1900-1999; approches et analyses; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; intersectionnalité; maternité; point de vue situé; premier cycle; périodes historiques; ressource en ligne; thématiques

New feminist criticism: art, identity, action - Frueh, Joanna; Langer, Cassandra; Raven, Arlene; Frueh, Joanna; Langer, Cassandra; Raven, Arlene (IconEditions, 1994)
This anthology of fifteen timely articles offers a wide range of feminist criticism sparked by ideas and events of the 1980's and 1990's. The articles consider culture, language, race, identity, sexuality, gender, creativity, aging and other issues. Though different in methodology, the writings are united by their common interest in feminism as a vehicule for intellectual exploration and individual communication and understanding. In their revisionary approaches, the contributors offer exciting new insights into the complex interaction between women and cultures, questionning inclusion as well as exclusion. "New Feminist Criticism" presents the unfinished and ongoing agenda of feminism in art, society and culture.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; art contemporain; art féministe; arts; corps; cours; critique d'art; discipline; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; intersectionnalité; premier cycle; périodes historiques; race; thématiques; vieillesse